Correction: Triple-negative breast cancer suppressive activities, antioxidants and pharmacophore model of new acylated rhamnopyranoses from Premna odorata. Issue 8 (22nd January 2021) - Elmaidomy, Abeer H.; Mohammed, Rabab; Owis, Asmaa I.; Hetta, Mona H.; AboulMagd, Asmaa M.; Siddique, Abu Bakar; Abdelmohsen, Usama Ramadan; Rateb, Mostafa E.; El Sayed, Khalid A.; Hassan, Hossam M.
Abstract : Correction for 'Triple-negative breast cancer suppressive activities, antioxidants and pharmacophore model of new acylated rhamnopyranoses from Premna odorata ' by Abeer H. Elmaidomy et al., RSC Adv., 2020, 10, 10584–10598. DOI: ; 10.1039/D0RA01697G